Impersonal Presences: tones of human in the landscape-scene - Ferrer (Universidade Federal de São João del-Rei ‒ UFSJ, São João del-Rei/MG, Brazil), Maria Clara (Revista Brasileira de Estudos da Presença, 2022)
Considered as an acting feature, presence is generally approached from the actor’s perspective. Disrupting this conception, this work intends to grasp presence as a relational, not a personal quality. For this purpose, two performances will be analyzed: Heiner Goebbels’s Stifters Dinge and Claude Régy’s Variations on death. Created as landscapes, both performances develop a non-anthropocentric aesthetics of the scene and allow envision presence as a perception phenomenon and from the point of view of the audience activity.